The Role Of Media Resources In Shaping The Educational Process Of Future Teachers: Peran Sumber Daya Media dalam Membentuk Proses Pendidikan Guru Masa Depan - Abdumannonovna, Juraeva Buvsara (Indonesian Journal of Education Methods Development, 2022)
After gaining independence, the country pays great attention to the training of qualified specialists. The training of highly qualified specialists is directly related to the strengthening of the material, technical and information base of educational institutions, the creation of high-quality textbooks, teaching aids, electronic textbooks and lecture notes, and the creation of electronic libraries. Wide access to modern knowledge, effective use of new information technologies in improving the education system has become a requirement of today.